2022
DOI: 10.1007/s00392-022-02020-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of catheter ablation for Brugada syndrome: an updated systematic review

Abstract: Background Patients with Brugada syndrome (BrS) may experience recurrent ventricular arrhythmias (VAs). Catheter ablation is becoming an emerging paradigm for treatment of BrS. Objective To assess the efficacy and safety of catheter ablation in BrS in an updated systematic review. Methods We comprehensively searched the databases of Pubmed/Medline, EMBASE, and Cochrane Central Register of Controlled Trials from inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Despite its complex and invasive nature necessitating general anaesthesia, this study demonstrates a favourable safety profile for epicardial ablation. Major complications were rare, consistent with previous studies from experienced centres, 5–9 , 13–15 , 24 but widespread adoption of this complex procedure could carry certain risks, and selection of patients is indeed crucial. Notably, the safety of the ajmaline test, especially the initial test with the substrate remaining intact, holds paramount significance.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite its complex and invasive nature necessitating general anaesthesia, this study demonstrates a favourable safety profile for epicardial ablation. Major complications were rare, consistent with previous studies from experienced centres, 5–9 , 13–15 , 24 but widespread adoption of this complex procedure could carry certain risks, and selection of patients is indeed crucial. Notably, the safety of the ajmaline test, especially the initial test with the substrate remaining intact, holds paramount significance.…”
Section: Discussionsupporting
confidence: 87%
“…Positive outcomes from epicardial substrate ablation in high-risk symptomatic BrS populations, as documented in previous studies, have been marred by several limitations. 9 , 13–15 , 23 , 24 These include varying learning curves across centres, diverse sample sizes, treatment heterogeneity, a range of mapping/ablation protocols potentially impacting substrate identification and ablation efficiency, variable follow-up durations, different data collection methodologies, and notably, a lack of control groups. We aimed to address these constraints by adopting a uniform mapping/ablation technique, utilizing ajmaline infusion, consistent long-term follow-ups, and introducing a no-RFA group for a thorough analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of ablation in BrS found that in 388 patients, VF was non-inducible in 87.1% of patients after ablation, and resolution of type 1 ECG was seen in 74.5% [66]. Recurrent VA was seen in 17.6%.…”
Section: Brugada Syndromementioning
confidence: 99%